Satisfaction of road tolling by road users: A case study of Accra – Tema motorway - Osei, Samuel (2021)
A thesis submitted to the Department of Construction Technology and Management, College of Arts and Built Environment, in partial fulfillment for the requirements for the Award of Master of Science.